IoT-Enabled Fire Detection and Alert System Leveraging HSV Thresholding - Jebanesan, Bevan; R., Umamaheswari (Journal of Ubiquitous Computing and Communication Technologies, 2024)
Fire detection plays an important role in minimizing damage caused by forest fires and enhancing response times. In this proposed study, a real-time fire detection system using a USB camera and Raspberry Pi, has been developed utilizing the concepts of IoT and image processing. The system continuously monitors the environment for the presence of fire by analysing video frames captured by the camera. The HSV colour space model is utilized to detect fire-like colours based on predefined thresholds, ensuring accurate identification of fire regions. Upon detection, the system triggers an alarm, retrieves geolocation data, and sends real-time alerts to a designated webpage, providing the fire’s exact location and a notification for immediate action. This approach eliminates the need for manual intervention, making it suitable for deployment in high-risk areas. The system’s modular design allows for integration with additional technologies such as automated fire extinguishing systems or GSM-based notifications, expanding its potential applications in real-world scenarios.